One health in India: Time to act together - PANKAJ DHAKA; J S BEDI; YASHPAL SINGH MALIK (Indian Journal of Animal Sciences, 2021)
The emerging public health issues of 21st century have clearly warned us that the efficient tackling of these threats need to be done in collaborative manner between relevant public health professionals under the umbrella of One Health. The concept of One Health is longstanding; however, it is gaining due momentum across the globe, especially in context of tackling emerging zoonoses. India remains vulnerable to many of emerging health threats due to demographic, socio-economic and other factors related with globalization, climate change and related biodiversity losses. In India, the various public health agencies which includes human, animal and environmental health professionals have contributed joint efforts in recent past to confront the One Health related issues. However, the bridging of professional silos to act more synergistically need further sustained efforts from all the stakeholders, including policy makers.